Resistência e potenciais elétricos para aterramento de um cabo horizontal situado na primeira camada considerando o solo com qualquer número de camadas - Silva, Elder Luiz Rodrigues (2015)
This paper presents a mathematical method that enables the achievement of the grounding resistance and the potential of the soil surface, generated by a grounding system, it consists of a buried cable horizontally. The grounding is present in the first layer of soil, assuming a soil composed of \"n\" horizontal layers. From this mathematical model a computer program developed to calculate the ground resistance and potential surface of the horizontal cable. For the validation of this mathematical model several experimental tests were performed, allowing the theoretical and experimental evidence. Simulations are also conducted to observe the influence of the layers in order ro determinate the grounding resistance and surface potentials, and also the influence on the accuracy of soil stratification into horizontal layers.